Peranan Badan Permusyawaratan Desa dalam Perencanaan Pembangunan Desa - Yoga Teja Wiguna; Rosmala Dewi; Nina Angelia (Universitas Medan Area, 2017)
Village development planning is very important, because from this development plan the direction of village development is determined. The aspirations of the community in the village development planning process are very much needed, so that it has become an obligation of the village government to accommodate community aspirations in the development planning process in the village. The aspirations of the community can be accommodated by involving the Village Consultative Body (BPD), because basically the Village Consultative Body (BPD) is a means for village communities to channel their aspirations to assist village government in the development planning process in the village. The research method used in this study is qualitative research methods, in which the process of data collection is done through observation, interviews, and documentation studies on informants who are considered to have the potential to provide information about the role of Village Consultative Bodies (BPD) in the development planning process in Bandar Village Klippa. From the results of the research that has been done, the Village Consultative Body (BPD) in Bandar Klippa Village has carried out its functions and duties well as a working partner of the Village Head and also to accommodate and channel community aspirations so that the development planning desired by the community is created. However, the Village Consultative Body (BPD) in Bandar Klippa Village was less active in coming directly to absorb and gather aspirations from the community.